Evaluation of bone, nutrition, and physical function in Shorinji Kempo athletes - Otani T (Open Access Journal of Sports Medicine, 2012)
Sachiko Sumida,1,2 Jun Iwamoto,3 Naoto Kamide,4 Toshiro Otani1,3,51Graduate School of Health Management, Keio University, 2Sports Medicine Research Center, Keio University, Kanawaga; 3Institute for Integrated Sports Medicine, School of Medicine, Keio University, Tokyo, 4School of Allied Health Sciences, Kitasato University, Kanagawa, 5Faculty of Nursing and Medical Care, Keio University, Kanawaga, JapanAbstract: The objectives of this study were to reveal the proportion of Shorinji Kempo athletes who had suffered fractures related to sports activities, and to evaluate bone mass, bone turnover, nutritional status, and physical function in these athletes. A medical examination was carried out for 16 Shorinji Kempo collegiate athletes. Seven athletes (43.8%) had experienced a sports-related traumatic fracture during Shorinji Kempo practice. Four athletes (25.0%) had a lower speed of sound (% young adult mean < 100%), and five athletes (31.3%) had higher levels of urinary cross-linked N-terminal telopeptides of type 1 collagen (a bone turnover marker) than the age-adjusted standard values. All the athletes had a lower daily calcium intake than the adequate intake, 12 (75.0%) had a lower daily vitamin D intake, and 15 (93.8%) had a lower daily vitamin K intake. Significant positive correlations were found between the vertical jump height, and the daily energy, and protein intakes. Results suggest that fractures are a common injury in Shorinji Kempo athletes, and that some Shorinji Kempo athletes need to improve their bone mass, bone metabolism, and nutritional status in order to strengthen bone and improve physical function.Keywords: medical checkup, Shorinji Kempo, fracture, nutrition; physical function